Ethical Leadership in Tech Startups: Managing Growth Without Compromising Values - Sarfan, Laode; Rudi Alhempi, Raden (PT. Multidisciplinary Press Indonesia, 2024)
This study examines the impact of ethical leadership practices, organizational culture, and employee engagement on the business growth of Gojek’s driver-partners and merchant partners in Padang. Using a quantitative approach, data were collected from a sample of 63 participants through random sampling. The analysis, conducted using SPSS, included t-tests, F-tests, and R² tests to assess the relationships between the independent variables (ethical leadership, organizational culture, and employee engagement) and the dependent variable (business growth). The results show that ethical leadership practices, organizational culture, and employee engagement have a significant positive influence on business growth, collectively explaining 58.5% of its variance. Ethical leadership emerged as the strongest predictor, followed by organizational culture and employee engagement. The findings suggest that fostering ethical, transparent leadership and a positive organizational culture, alongside encouraging active partner engagement, are crucial for the sustainable growth of Gojek’s driver-partners and merchants. This research provides practical insights for platform-based companies on improving partnership management strategies. However, further investigation is needed to explore additional factors influencing business growth in the gig economy context.